Artificial Selection Trend of Wheat Varieties Released in Huang-Huai-Hai Region in China Evaluated Using DUS Testing Characteristics - Wang, Liyuan; Zheng, Yongsheng; Duan, Lili; Wang, Mumu; Wang, Hui; Li, Hua; Li, Ruyu; Zhang, Han (Frontiers in Plant Science, 2022)
Wheat has been widely cultivated all over the world. In China, the number of approved wheat varieties has steadily grown since 2010, with the most notable trend in Huang-Huai-Hai region. Distinctiveness, uniformity and stability (DUS) are the prerequisites for a new wheat variety to obtain release permit. Yet, few reports are available on DUS testing characteristics of released wheat varieties. Here, thirty-two DUS testing characteristics of 195 wheat varieties released in Huang-Huai-Hai region were investigated to study their artificial selection trend. The results showed that the means, ranges and coefficients of variation for eight measured characteristics varied greatly, among which the number of sterile spikelets had the largest variation coefficient of all three wheat growing areas in Huang-Huai-Hai region. The difference of plant height between the three wheat growing areas was the most significant. The mean plant height in northern winter wheat area was the largest, while that in south Huanghuai was the smallest. The released varieties of the three wheat growing areas in the region had similar artificial selection trend in some characteristics. For instance, flag leaf length and flag leaf width, grain number per ear and grain volume weight showed an overall upward trend, while the plant height decreased gradually. The clustering results based on DUS testing characteristics showed that artificial selection of characteristics was consistent with ecological adaptation and breeding process as well as pedigree sources. Our findings indicated that with the current breeding objectives, the selection of some non-economic characteristics of wheat varieties, such as awn color, stem color and glume color, seemed to be able to enrich the genetic diversity of varieties in Huang-Huai-Hai region. These results could provide guidance for subsequent wheat breeding and production in this region, as well as screening similar varieties and determining the distinctness of applied varieties in DUS testing.